Appropriateness of DOAC Prescribing Before and During Hospital Admission and Analysis of Determinants for Inappropriate Prescribing - Moudallel, Souad; Steurbaut, Stephane; Cornu, Pieter; Dupont, Alain (Frontiers in Pharmacology, 2018)
Background and Objectives: Appropriate dosing of direct oral anticoagulants (DOACs) is required to avoid under- and overdosing that may precipitate strokes or thromboembolic events and bleedings, respectively. Our objective was to analyze the appropriateness of DOAC dosing according to the summaries of product characteristics (SmPC). Furthermore, determinants for inappropriate prescribing were investigated. Methodology: Retrospective cohort study of hospitalized patients aged ≥60 years with at least one DOAC intake during hospital stay. Descriptive analyses were used to summarize the characteristics of the study population. Chi-square test was used to evaluate differences between DOACs. Binary logistic regression analysis was performed to assess determinants for inappropriate prescribing. Results: For the 772 included patients, inappropriate dosing occurred in 25.0% of hospitalizations with 23.4%, 21.9% and 29.7% for dabigatran, rivaroxaban and apixaban, respectively (p=0.084). Underdosing was most prevalent for apixaban (24.5%) compared to dabigatran (14.0%) and rivaroxaban (12.8%), p<0.001. In 67.1% (apixaban), 26.7% (dabigatran) and 51.2% (rivaroxaban) of underdosed DOAC cases according to the SmPC, the dose would be considered appropriate according to the European Heart Rhytm Association (EHRA) guidelines. Overdosing was observed in 4.5% (apixaban), 4.7% (dabigatran) and 7.7% (rivaroxaban) of patients. For all DOACs, our analysis showed an age ≥80 years (p=0.036), use of apixaban (p=0.026), DOAC use before hospitalization (p=0.001), intermediate renal function (p=0.014) and use of narcotic analgesics (p=0.019) to be associated with a higher rate of inappropriate prescribing. Undergoing surgery was associated with a lower odds of inappropriate prescribing (p=0.012). For rivaroxaban, use of medication for hypothyroidism (p=0.027) and the reduced dose (p<0.001) were determinants for inappropriate prescribing. Treatment of venous thromboembolism was associated with less errors (p=0.002). For apixaban, severe renal insufficiency (p<0.001) and initiation in hospital (p=0.016) were associated with less and the reduced dose (p<0.001) with more inappropriate prescribing. No determinants were found in the dabigatran subgroup. Conclusions: Inappropriate DOAC prescribing is frequent with underdosing being the most common drug related problem when using the SmPC as reference. More appropriate prescriptions were found when taking the EHRA guidelines into account. Analysis of determinants of inappropriate prescribing yielded insights in the risk factors associated with inappropriate DOAC prescriptions.